Simons Observatory: Predeployment Performance of a Large Aperture Telescope Optics Tube in the 90 and 150 GHz Spectral Bands - Carlos E. Sierra; Kathleen Harrington; Shreya Sutariya; Thomas Alford; Anna M. Kofman; Grace E. Chesmore; Jason E. Austermann; Andrew Bazarko; James A. Beall; Tanay Bhandarkar; Mark J. Devlin; Simon R. Dicker; et al. (The Astrophysical Journal Supplement Series)
The Simons Observatory will map the temperature and polarization over half of the sky at millimeter wavelengths in six spectral bands from the Atacama Desert in Chile. These data will provide new insights into the genesis, content, and history of our Universe, the astrophysics of galaxies and galaxy clusters, objects in our solar system, and time-varying astrophysical phenomena. This ambitious new instrument suite, initially comprising three 0.5 m diameter small aperture telescopes and one 6 m diameter large aperture telescope, is designed using a common combination of new technologies and new implementations to realize an observatory significantly more sensitive than the previous generation. In this paper, we present the predeployment performance of the first mid-frequency “optics tube,” which will be fielded on the large aperture telescope with sensitivity to the 90 and 150 GHz spectral bands. This optics tube contains lenses, filters, detectors, and readout components, all of which operate at cryogenic temperatures. It is one of seven that form the core of the large aperture telescope receiver in its initial deployment. We describe this optics tube, including details of comprehensive testing methods, new techniques for beam and passband characterization, and its measured performance. The performance metrics include beams, optical efficiency, passbands, and forecasts for the on-sky performance of the system. We forecast a sensitivity that exceeds the requirements of the large aperture telescope with greater than 30% margin in each spectral band and predict that the instrument will realize diffraction-limited performance and the expected detector passbands.